2005
DOI: 10.1007/s00198-005-1844-1
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of serum osteoprotegerin to bone mass and vertebral fractures in postmenopausal women

Abstract: Regulation of osteoclastic activity is critical for understanding bone loss associated with the postmenopausal period. In vitro and animal studies have revealed the role of OPG as a decoy receptor that neutralizes the effect of RANKL on the differentiation and activation of osteoclasts. However, the role of the OPG-RANKL system in postmenopausal osteoporosis is controversial. Thus, the aim of this study was to investigate the relationship among circulating levels of OPG, RANKL, bone turnover markers (BTM), bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
2
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 28 publications
6
71
2
5
Order By: Relevance
“…Neither OPG nor RANKL predicted 5 to 10 year change in BMD. The absence of a positive association of OPG with BMD in women who were not using estrogen is concordant with five of six previous studies (3,11,14,16,21,28). Only one prior study explicitly assessed women using estrogen.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Neither OPG nor RANKL predicted 5 to 10 year change in BMD. The absence of a positive association of OPG with BMD in women who were not using estrogen is concordant with five of six previous studies (3,11,14,16,21,28). Only one prior study explicitly assessed women using estrogen.…”
Section: Discussionsupporting
confidence: 85%
“…OPG levels reported here are within the wide range published in other studies. Mean values of OPG (for assays that detect all OPG forms) have ranged from 10 to 246 pg/ml (3,(14)(15)(16)21), with the exception of one study reporting 1359 and 1229 pg/ ml for pre-and postmenopausal women respectively (28). Wide ranges in reported values likely reflect differences in study populations, collection and storage methods, assay detection levels, and improved detection levels in newer assays (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the literature presents conflicting results concerning the period after menopause, when bone loss is related to favoring RANKL activity over that of OPG. In a cohort study, Mezquita-Raya et al 21 and Chiba et al 22 found no correlation between OPG and bone resorption markers in women, regardless of their menopause status. According to the results, this study also demonstrated that the expression of bone markers during repair of autogenous bone grafts was not altered by estrogen deficiency.…”
mentioning
confidence: 94%